Effects of different audiovisual landscapes in bamboo forest space on physical and mental restorative potential of university students: based on eye-tracking experiments - Zhu, Chunyan; Feng, Xindi; Luo, Jinming; Fu, Shanshan; Li, Tianhui; Wang, Wei; Li, Xi (Frontiers in Forests and Global Change, 2024)
With its unique audio-visual environment, bamboo forest space is a natural healing place for urban residents to reduce physical and mental stress and alleviate fatigue, which exerts a significant restorative effect and helps to promote the vigorous development of outdoor recreation activities. Unfortunately, restorative research on the audiovisual perception of bamboo forest space is still insufficient. In this study, we conducted field research on bamboo forest spaces in the Southern Sichuan Bamboo Sea, and collected audiovisual materials of four types of bamboo forest spaces (pathway type, cultural type, ornamental type, and recreational type). The four types of spatial photographs were combined with three types of sound (silent sound, background sound, background sound + wind-blown bamboo sound), and eye-tracking experiments were utilized to investigate the physical and mental restorative effects of different audiovisual features of bamboo forest spaces on college students. The results showed that: (1) the visual restorative properties of recreational-type and ornamental-type bamboo spaces were better than those of pathway-type and cultural-type spaces. (2) The sound of wind-blown bamboo sound, the sound of water flowing in the bamboo forest and the sound of chirm in the bamboo forest can significantly increase the subjective restorative properties of the bamboo forest space, and reduce the number of fixations and the average pupil diameter of the space. (3) The soundscape has a guiding effect on people's visual attention, and the sound of windblown bamboo can increase people's attention to natural elements. (4) The extensibility of the bamboo forest space is positively correlated with the number of fixations, and the fascination is negatively correlated with the average saccade amplitude. These findings provide a reference basis for the optimized design of audiovisual restorative environment in bamboo forest space in the future.